Density functional theory assisted composition engineering of PtxRhyNiz dendritic mesoporous nanoparticles boosting ethanol electro-oxidation catalysis - Chang Liu; Xinwei Wen; Xin Ran; Long Yang; Lei Li; Qing Qu (Chemical Engineering Journal, 2026)

Macroscopic crack ratio as a structural surrogate linking linear filtration and nonlinear expression in sludge dewatering - Yi-Wen Yuan; Hao-Ran Chen; Zhi-Hao Liu; Shi-Yu Ren; Chang-Ji Huang; Raymond Jianxiong Zeng; Hou-Feng Wang (Process Safety and Environmental Protection, 2026)

Sulfate as a regulator of Bacteroides thetaiotaomicron glutamate decarboxylase: Elucidating the bipartite binding and regulation mechanism - Shujun Liu; Yulu Wang; Boting Wen; Ran Ran; Haiyan Yu; Abeer Mohamed; Xue Han; Zhen Li; Fengjiao Xin (Food Chemistry, 2026)

Chemotactic sensing of extracellular antibiotic resistance genes enables their efficient removal by Stutzerimonas stutzeri - Ran Chai; Juan Liu; Shuhong Wang; Wen Yang; Jiaxiang Guo; Dan Zhu; Haifeng Wang; Xinding Yao; Liyou Qiu (Journal of Hazardous Materials, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Impact of waste biomass binders on the pelletizing, combustion, and engineering feasibility of sludge–coal slime co-pelletized fuel - Hao-Ran Chen; Yi-Wen Yuan; Zhi-Hao Liu; Chang-Ji Huang; Shi-YuS Ren; Hou-Feng Wang; Raymond Jianxiong Zeng (Environmental Research, 2026)

Ultrathin wide-bandgap niobate for high-performance photodetection and information encryption - Xiaoqiang Feng; Xiaolin Zhang; Ran Liu; Xiaolong Guo; Yuchan Hu; Lizhikun Gong; Yiling Yu; Lei Yin; Yao Wen; Yuchen Cai; Ruiqing Cheng; Jun He (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Screening and identification of soybean antioxidant peptides using Fe3O4-Modified carbon fibers - Xiao-Feng Chen; Xiang-Yu Huang; Hao-Ran Liu; Li Ding; Li Wen; Xu-Feng Wang; Zhou Xu; Yun-Hui Cheng; Mao-Long Chen (Food Bioscience, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

Spatial management of riverine methane (CH4) emissions based on landscape drivers in the Yangtze River Basin - Shuoqi Cheng; Yingzheng Fan; Wen Fang; Ran Yin; Yao Pan; Qiuju Liu; Xinkun Ren; Jinfeng Wang (Journal of Environmental Management, 2026)

Biodegradable microplastics-induced free-living nitrogen fixation enhancement and diazotrophic community differentiation in soils - Yujuan Han; Peixin Gao; Jiping Song; Yanning Li; Xiao Wang; Ning Yang; Xu Zhao; Bo Liu; Chuankun Zhang; Ran Li; Dan Wen; Ying Teng (Journal of Environmental Management, 2026)

Urbanisation accelerates carbon cycling and greenhouse gas emissions along a river-ocean continuum in the humid subtropics - Ho Wen Lo; Henry Charles James Thomas; Nga Man Chung; Jiao Liu; Qianqian Yang; Benoit Thibodeau; Lishan Ran (Environmental Research, 2026)

Catalyzed in-situ amination of support layer for thermally stable forward osmosis membranes in industrial dyeing wastewater concentration - Qin Zheng; Meng-ran Xu; Dai-feng Song; Wen-shi Liu; Hao-Ran Zuo; Ming Duan (Desalination, 2026)

Digested soybean proteins and peptides differentially boost HT-29 enterocyte adhesion to Lactobacillus strains: A transcriptomic mechanism study - Yuan Liu; Ran Wang; Yanchao Wen; Siyu Chen; Xiaohan Zhang; Xinqi Liu; Chi Zhang (Food Bioscience, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Hydrogen sulfide-based nanotheranostics: A multifunctional platform for cancer diagnosis and therapy - Wen Ran; Yan Zhao; Ruiping Huang; Enhao Cao; Junjie Zhou; Jiang Yu; Hongzhuo Liu; Yongjun Wang (Chemical Engineering Journal, 2026)

Low-temperature mineral engineering stabilizes anchored cobalt sites for ultrafast antibiotic destruction via electron transfer-driven radical/nonradical synergy - Liyao Ren; Ran Liu; Runbin Zeng; Lingling Cao; Wenyu Wang; Xuguang Li; Xing Xu; Yanxia Zhao; Liangguo Yan; Yanfei Li; Wen Song (ENGINEERING Environment, 2026)

Structure-Oriented Kriging for High-Fidelity Acquisition Footprint Suppression - Liang Huang; Ming-ran Liu; Wen-chao Su; Jiang-yun Zhang; Xu-hui Zhou; Guo-xu Shu; Shou-dong Huo (Applied Geophysics, 2026)

CO2 and CH4 emissions from subtropical aquaculture ponds under different management practices - Qianqian Yang; Lishan Ran; Ho Wen Lo; Tong Zhang; Shuai Chen; Yongli Zhou; Boyi Liu; Yuxin Li (Aquaculture, 2026)

Boosting coalbed methane recovery through nanofluid-mediated pore and interfacial regulation - Jiajia Zhao; Shixiang Tian; Yihong Wen; Ting Liu; Tong Liu; Xuan Zhang; Tengfei Ma; Qican Ran (Process Safety and Environmental Protection, 2026)

A chlorinated 2-(2-phenylethyl)chromone in artificial agarwood as a DRD5 agonist and mediates the cAMP/Ca²⁺ signaling pathway to intervene in the growth and proliferation of gastric cancer cells - Zi-Xiao Jiang; Jian Feng; Wen-Cheng Hou; Mei-Ran Wang; Shu-Nan Zhang; Yang-Yang Liu (Phytochemistry Letters, 2026)

Bioinformatics-based discovery of a new norsesquiterpenoid from agarwood targeting CHRM2 and regulating the PI3K-Akt pathway in liver cancer - Zi-Xiao Jiang; Jian Feng; Wen-Cheng Hou; Mei-Ran Wang; Shu-Nan Zhang; Hao-Jie Liang; Yang-Yang Liu (Phytochemistry Letters, 2026)

A wind energy-biomass-coal synergistic system for producing multiple products based on the carbon and nitrogen cycles and its optimization - Yipeng Zhang; Zhongwen Song; Shuo Wen; Ran Li; Guilian Liu (Journal of Cleaner Production, 2026)

Molecularly imprinted polymers-based magnetic CoFe oxides nanozyme for the removal of Staphylococcus aureus and label-free quantitative detection - Jing Liu; Ran Chen; Jing-Wen Chen; Shao-Bo Li; Yue-Jie Li; Yong-Fu Huang; Zhi-Bin Chen; Li Li (Chemical Engineering Journal, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Green synthesis of photo-Fenton-active Fe-BDC from waste polyester for co-enhancing solar interfacial evaporation with organic contaminant remediation - Jie Liu; Hangyuan Du; Huiyue Wang; Hongrun Zhu; Xueying Wen; Xingpei Yu; Junhao Ai; Ran Niu; Nan Yao; Jiang Gong (Chemical Engineering Journal, 2025)

Assessment of flood risk in jinsha river basin based on land use value and PSR model - Xiao Chen; Ran Zhai; Wen Fang; Liwen Xu; Lili Liang; Juanru Yang; Hanlin Man; Zhenyu Lv; Chao Wang; Deng Liu; Mengqing Cui (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

Unraveling the flavor formation mechanisms of Wanxi dry-cured goose: Microbiomics, metabolomics, and flavoromics study - Ran Wang; Di Liu; Zhenwei Wang; Changhong Wu; Che Shen; Jingnan Lu; Wen Nie; Dekuan Wei; Kezhou Cai; Baocai Xu (Food Research International, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Defect engineering toward binary spinel ZnCo2O4 for boosting electrocatalytic nitrate reduction to ammonia - Qingsong Lai; Zhaomeng Liu; Ahmad Akasa; Xiran Zhao; Ran Wei; Xuan-Wen Gao; Teuku Muhammad Al Wafi; Qinfen Gu; Wen-Bin Luo (Chemical Engineering Journal, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Strip application of organic fertilizer in the root zone increases the substitution ratio of chemical nitrogen and sunflower yield in saline-alkali soil - Ran LI; Shujuan WANG; Jia LIU; Erzhen LI; Junxia MIAO; Xiaoliang WEN; Jing YANG; Lizhen XU; Binrui LI; Cunwang JIN; Yan LI; Yonggan ZHAO (Pedosphere, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Effectiveness of bioretention system with saturated zone and different dry–wet alterations on nitrogen removal: performance and microbial community - Ran Li; Binyu Lu; Wen-wen Liu; Zebing Li; Yi-Ming Kuo (Environmental Geochemistry and Health, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Knockdown of RUNX2 Attenuated A1 Astrocyte Overactivation, Brain Injury, and Cerebral Edema During Ischemic Stroke - Zhibing Ai; Wei Huang; Wei Hu; Ran An; Gongwen Lei; Wen Gu; Xiaoqin Peng; Yong Liu (NeuroMolecular Medicine, 2025)

Tracking phycocyanin dynamics in East Lake using Landsat-8 and generalized additive models: impact of COVID-19 and conservation efforts - Jincan Tang; Wen-Wen Liu; Ran Li; Enmin Zhao; Yi-Ming Kuo (Environmental Monitoring and Assessment, 2025)

Robust distributed autonomous orbit determination for LEO mega constellation based on inter-satellite ranging and astronomical measurement - Yuanlan Wen; Ping Zeng; Chengxin Ran; Zhetao Zhang; Xiufeng He; Lina He; Zhaokui Wang; Fucheng Liu (Advances in Space Research, 2025)

Unraveling the secrets of probiotic adhesion: An overview of adhesion-associated cell surface components, adhesion mechanisms, and the effects of food composition - Ran Wang; Yuan Liu; Yanchao Wen; Siyu Chen; Xiaohan Zhang; Chi Zhang; Xinqi Liu (Trends in Food Science & Technology, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Mechanisms of soybean proteins and peptides regulating the adhesion of Lacticaseibacillus rhamnosus GG and Lactiplantibacillus plantarum K25 to intestinal cells: A Comparative Study - Yinxiao Zhang; Yanchao Wen; Chi Zhang; Yuan Liu; Ran Wang; He Li; Xinqi Liu (Food Bioscience, 2025)

Exploring the anti-inflammatory potential of Lacticaseibacillus paracasei postbiotics: Mechanistic insights and functional components - Yuhang Sun; Zhe Sun; Bing Fang; Ran Wang; Yue Liu; Jingyu Li; Hanglian Lan; Wen Zhao; Wei-Lian Hung; Ming Zhang (Food Bioscience, 2025)

Study on the Spatial and Temporal Evolution Law of Large-Size Fracture Propagation in Deep Coalbed Based on Acoustic Emission Technology - Zhihong Zhao; Tianyu Wu; Jianchun Guo; Jiale He; Xiaoyong Wen; Yi Liu; Ran Zhang (Rock Mechanics and Rock Engineering, 2025)

Controls of paleogeomorphology on organic matter accumulation as recorded in Ordovician–Silurian marine black shales in the western South China Block - Feng Liang; Qun Zhao; Qin Zhang; Yuman Wang; Shangwen Zhou; Zhen Qiu; Wen Liu; Bo Ran; Tong Sun (Marine and Petroleum Geology, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Suitable water management improving cold tolerance of rice seedlings - Qiang Zhang; Feng Wen; Bingbing Li; Zhi Li; Zhenjiang Wu; Xu Kuang; Guilong Yu; Xiangchen Liu; Yang Hu; Yuchen Zhang; Ran Yu; Lingling Ding; et al. (Cereal Research Communications, 2024)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Green conversion of waste polyester into few-layer graphene for interfacial solar-driven evaporation and hydroelectric electricity generation - Guixin Hu; Huiyue Wang; Huajian Liu; Xueying Wen; Jie Liu; Zifen Fan; Lijie Liu; Yan She; Ran Niu; Jiang Gong (Journal of Cleaner Production, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Concentration and activation biresponsive strategy in one analysis system with simultaneous use of G4 structure-specific signal probe and enzyme-catalyzed reaction - Yu-Shu Li; Chun-Feng Feng; Hao-Ran Chen; Wei-Guo Yang; Fei Liu; Ming-Li Su; Ruo Yuan; Li-Qun Zhang; Wen-Bin Liang (Analytica Chimica Acta, 2024)

Investigating the different effects of soybean proteins and peptides on the adhesion capacity of Limosilactobacillus reuteri LR08 and Escherichia coli JCM1649 - Yanchao Wen; Yinxiao Zhang; Ran Wang; Yuan Liu; Jingyi Wang; Chi Zhang; Xinqi Liu (Food Bioscience, 2024)

Macrophage-Targeted multifunctional nanoparticles for detection and treatment of intraplaque hemorrhage - Haiyang Wang; Min Zheng; Yushi Chen; Long Cheng; Xiaotong Qi; Huilin Yu; Jianming Sun; Junjie Liu; Ruoyao Wang; Yaqin Hu; Tao Lin; Ying Zhang; et al. (Chemical Engineering Journal, 2024)

Involvement of CgHSFB1 in the regulation of self-incompatibility in ‘Shatian’ pummelo - Chenchen Liu; Xin Zheng; Jianbing Hu; Qiang Xu; Hao Wen; Zhezhong Zhang; Ran Liu; Xiangling Chen; Zongzhou Xie; Junli Ye; Xiuxin Deng; Lijun Chai (Plant Molecular Biology, 2024)

Effect of soybean proteins and peptides on the growth and adhesive ability of Limosilactobacillus Reuteri DSM17938 - Yan Wang; Jingyi Wang; Yanchao Wen; Yinxiao Zhang; Ran Wang; Yuan Liu; He Li; Yan Li; Chi Zhang (Archives of Microbiology, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Upcycling of waste poly(lactic acid) into crumped carbon nanosheet towards high-performance interfacial solar-driven evaporation - Jie Liu; Zifen Fan; Huajian Liu; Lijie Liu; Xueying Wen; Huiyue Wang; Ran Niu; Huina Wang; Jiaji Cheng; Jiang Gong (Journal of Environmental Chemical Engineering, 2024)

Transforming waste polyester into porous carbon polyhedron for interfacial solar steam and hydrovoltaic electricity co-generation - Huajian Liu; Lijie Liu; Zifen Fan; Jie Liu; Huiyue Wang; Xueying Wen; Guixin Hu; Kuankuan Liu; Ran Niu; Jiang Gong (Chemical Engineering Journal, 2024)

Different binding properties of odorant-binding protein 8 to insecticides in Orius sauteri - Zhe-Ran Wu; Yi-Wen Pei; Xiao-Qing Zhang; Min Lu; Xiao-Long Liu (Pesticide Biochemistry and Physiology, 2024)

The Alasu rock avalanche in the Tianshan Mountains, China: fragmentation, landforms, and kinematics - Qi-wen Lin; Yu-feng Wang; Qian-gong Cheng; Jing Huang; Hao-ran Tian; Guo-xiang Liu; Ke He (Landslides, 2024)

Dynamic response mechanism and precursor characteristics of gneiss rockburst under different initial burial depths - Dongqiao Liu; Jie Sun; Wen Meng; Manchao He; Chongyuan Zhang; Ran Li; Binghao Cao (Journal of Mountain Science, 2024)

Phenethyl isothiocyanate induces cytotoxicity and apoptosis of porcine kidney cells through Mitochondrial ROS-associated ERS pathway - Yuanyuan Zhu; Qiurong Xu; Ruili Zou; Sha Liu; Ran Tao; Shuiping Liu; Xiaowen Li; Lixin Wen; Jing Wu; Ji Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Retention Efficiencies of Vegetative Filter Strips in Reducing Agricultural Nonpoint Source Pollution in Jianghan Plain: Experiments and VFSMOD Modeling - Ran Li; Wen-wen Liu; Enmin Zhao; Yi-Ming Kuo (Water, Air, & Soil Pollution, 2024)

Chemodiversity transformation of organic matters in a full scale MBR-NF wastewater reclamation plant - Jinlan Yu; Ran Huo; Wei Liu; Xianghua Wen (Science of The Total Environment, 2023)

Effects of pile-fermentation on the aroma quality of dark tea from a single large-leaf tea variety by GC × GC-QTOFMS and electronic nose - Shuai Wen; Ronggang Jiang; Ran An; Jian Ouyang; Changwei Liu; Zhong Wang; Hongyu Chen; Xingchang Ou; Hongzhe Zeng; Jinhua Chen; Shili Sun; Junxi Cao; et al. (Food Research International, 2023)

Curcumin-loaded high internal phase emulsions alleviated dextran sulfate sodium-induced ulcerative colitis in mice via inhibiting inflammatory response and modulating gut microbiota - Ran Feng; Wen-Jie Liu; Bao-Cai Xu; Han Tao; Bao Zhang (Food Bioscience, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

OsBBX19-OsBTB97/OsBBX11 module regulates spikelet development and yield production in rice - Abdullah Shalmani; Uzair Ullah; Li Tai; Ran Zhang; Xiu-Qing Jing; Izhar Muhammad; Nadeem Bhanbhro; Wen-Ting Liu; Wen-Qiang Li; Kun-Ming Chen (Plant Science, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Moderate scale and realization potential of new citrus-planting business entities in hilly and mountainous areas in China - Xuan-yun Zhang; Shi-chao Zhang; Jing-yu Liu; Na Ran; Xiang Zhang; Qi-wen Ning (Journal of Mountain Science, 2023)

Zinc isotopic systematics of deep crustal xenoliths from the southeastern North China craton and implications for intra-crustal differentiation - Wen-Ran Liu; Ze-Zhou Wang; Sheng-Ao Liu (Lithos, 2023)

Selenium deficiency induced inflammation and apoptosis via NF-κB and MAPKs pathways in muscle of common carp (Cyprinus carpio L.) - Ran Xu; Jing-wen Cao; Tian-chao Xu; Tian-jing Liu; Meng-ran Zhu; Meng-yao Guo (Fish & Shellfish Immunology, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Particulate matter, nitrogen dioxide, and sulfur dioxide and their associations with allergic skin diseases: A systematic review and meta-analysis - Jin Huang; Wen-hao Zheng; Hong-chan Huang; Yi-guo Ran; Yi Liu; Ping Huang (Atmospheric Pollution Research, 2023)

Remote estimation of leaf water concentration in winter wheat under different nitrogen treatments and plant growth stages - Li He; Meng-Ran Liu; Shao-Hua Zhang; Han-Wen Guan; Chen-Yang Wang; Wei Feng; Tian-Cai Guo (Precision Agriculture, 2023)

QTL Detection for Internode Component Index in Wheat Using a RIL Mapping Population - Ran Qin; Tianhang Ma; Mingsu Cao; Xijian Liu; Xiaohan Zhou; Guimei Hu; Wen Zhong; Xiaohui Sun; Jingguo Xiao; Jiajin Dong; Wenchao Kong; Chunhua Zhao; et al. (Plant Molecular Biology Reporter, 2023)

Recent advancements in antibiotics containing wastewater treatment by integrated bio-electrochemical-constructed wetland systems (BES-CWs) - Shuang Luo; Zhi-Yuan Zhao; Ying Liu; Ran Liu; Wen-Zong Liu; Xiao-Chi Feng; Ai-Jie Wang; Hong-Cheng Wang (Chemical Engineering Journal, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Amendment-Enhanced Phytoextraction of Cadmium from Contaminated Soil Integrating with Ramie as Hyperaccumulator Plant - Zhen Zhang; Haotian Zhang; Kok Sin Woon; Xiaohu Zhu; Yuhong Sui; Zifeng Luo; Lili Chen; Xiaoming Yang; Junyi Gao; Hongping Wen; Ran Jing; Tongzhou Liu (Water, Air, & Soil Pollution, 2022)

Overexpression of a putative 12-oxophytodienoate reductase gene, EpOPR1, enhances acetylshikonin production in Echium plantagineum - Jiangyan Fu; Ran Ren; Suo Jin; Rongjun Fang; Zhongling Wen; Minkai Yang; Xuan Wang; Bao Liu; Tongming Yin; Guihua Lu; Yonghua Yang; Jinliang Qi (In Vitro Cellular & Developmental Biology - Plant, 2022)

Genome-wide association analysis of root length traits in Brassica napus at germination stage under sodium carbonate stress - Jindong Chen; Hao Zhang; Jiangqun Tong; Chunyue Liu; Jinghong Ran; Juan Tang; Jiaying Liu; Jing Wen; Changli Zeng; Heping Wan; Jinxiong Shen (Euphytica, 2021)

Genome-wide linkage mapping for canopy activity related traits using three RIL populations in bread wheat - Faji Li; Weie Wen; Jindong Liu; Shengnan Zhai; Xinyou Cao; Cheng Liu; Dungong Cheng; Jun Guo; Yan Zi; Ran Han; Xiaolu Wang; Aifeng Liu; et al. (Euphytica, 2021)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Dysregulation within the salience network and default mode network in hyperthyroid patients: a follow-up resting-state functional MRI study - Bo Liu; Li Wen; Qian Ran; Si Zhang; Junhao Hu; Mingfu Gong; Dong Zhang (Brain Imaging and Behavior, 2020)

Genome-wide survey and expression analyses of the GRAS gene family in Brassica napus reveals their roles in root development and stress response - Pengcheng Guo; Jing Wen; Jin Yang; Yunzhuo Ke; Mangmang Wang; Mingming Liu; Feng Ran; Yunwen Wu; Pengfeng Li; Jiana Li; Hai Du (Planta, 2019)

Interleukin-26 upregulates interleukin-22 production by human CD4+ T cells in tuberculous pleurisy - Min Zhang; Yi-Ran Niu; Jing-Yuan Liu; Xiao-Shan Wei; Xiao-Rong Wang; Lin-Lin Ye; Wen-Bei Peng; Jian-Chu Zhang; Xiao-Nan Tao; Qiong Zhou (Journal of Molecular Medicine, 2019)

The research progress in mechanism and influence of biosorption between lactic acid bacteria and Pb(II): A review - Derong Lin; Ran Ji; Dan Wang; Mengshi Xiao; Jingjing Zhao; Jinpeng Zou; Yutong Li; Tao Qin; Baoshan Xing; Yuan Chen; Peng Liu; Zhijun Wu; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Using generalized additive models to investigate factors influencing cyanobacterial abundance through phycocyanin fluorescence in East Lake, China - Yi-Ming Kuo; Jun Yang; Wen-wen Liu; Enmin Zhao; Ran Li; Liquan Yao (Environmental Monitoring and Assessment, 2018)

Potential health risk assessment through ingestion and dermal contact arsenic-contaminated groundwater in Jianghan Plain, China - Ran Li; Yi-Ming Kuo; Wen-wen Liu; Cheng-Shin Jang; Enmin Zhao; Liquan Yao (Environmental Geochemistry and Health, 2018)

Improving Cu(II) sorption by biochar via pyrolyzation under CO2: the importance of inherent inorganic species - Ran Wen; Bo Yuan; Yang Wang; Weimin Cao; Yuan Liu; Yi Jia; Qiang Liu (Environmental Science and Pollution Research, 2018)

Effects of different fertilizer application methods on the community of nitrifiers and denitrifiers in a paddy soil - Ran Duan; Xi-En Long; Yue-feng Tang; Jiong Wen; Shiming Su; Lingyu Bai; Rongle Liu; Xibai Zeng (Journal of Soils and Sediments, 2018)

Thermodynamically diverse syntrophic aromatic compound catabolism - Masaru Konishi Nobu; Takashi Narihiro; Miaomiao Liu; Kyohei Kuroda; Ran Mei; Wen‐Tso Liu (Environmental Microbiology, 2017)
Summary Specialized organotrophic Bacteria ‘syntrophs’ and methanogenic Archaea ‘methanogens’ form a unique metabolic interaction to accomplish cooperative mineralization of organic compounds to CH 4 and CO 2 . Due to challenges in cultivation of syntrophs, mechanisms for how their organotrophic catabolism circumvents thermodynamic restrictions remain unclear. In this study, we investigate two communities hosting diverse syntrophic aromatic compound metabolizers ( Syntrophus , Syntrophorhabdus , Pelotomaculum and an uncultivated Syntrophorhabdacaeae member) to uncover their catabolic diversity and flexibility. Although syntrophs have been generally presumed to metabolize aromatic compounds to acetate, CO 2 , H 2 and formate, combined metagenomics and metatranscriptomics show that uncultured syntrophs utilize unconventional alternative metabolic pathways in situ producing butyrate, cyclohexanecarboxylate and benzoate as catabolic byproducts. In addition, we also find parallel utilization of diverse H 2 and formate generating pathways to facilitate interactions with partner methanogens. Based on thermodynamic calculations, these pathways may enable syntrophs to combat thermodynamic restrictions. In addition, when fed with specific substrates (i.e., benzoate, terephthalate or trimellitate), each syntroph population expresses different pathways, suggesting ecological diversification among syntrophs. These findings suggest we may be drastically underestimating the biochemical capabilities, strategies and diversity of syntrophic bacteria thriving at the thermodynamic limit.

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Toxicity and accumulation of zinc pyrithione in the liver and kidneys of Carassius auratus gibelio: association with P-glycoprotein expression - Tao Ren; Gui-Hong Fu; Teng-Fei Liu; Kun Hu; Hao-Ran Li; Wen-Hong Fang; Xian-Le Yang (Fish Physiology and Biochemistry, 2017)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

Characterization of an extracellularly derived α-mannosidase from the liquid exudate of the sclerotia of Sclerotinia sclerotiorum (Lib.) de Bary - Zhengli Liu; Ran Wei; Wen He; Ying Ruan; Chunlin Liu (Antonie van Leeuwenhoek, 2015)

Ascomycotin A, a new citromycetin analogue produced by Ascomycota sp. Ind19F07 isolated from deep sea sediment - Yong-qi Tian; Xiu-ping Lin; Juan Liu; Kumaravel Kaliyaperumal; Wen Ai; Zhi-ran Ju; Bin Yang; Junfeng Wang; Xian-wen Yang; Yonghong Liu (Natural Product Research, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Determination of royal jelly freshness by ELISA with a highly specific anti-apalbumin 1, major royal jelly protein 1 antibody - Li-rong Shen; Yi-ran Wang; Liang Zhai; Wen-xiu Zhou; Liang-liang Tan; Mei-lu Li; Dan-dan Liu; Fa Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Genetic data provided by 21 autosomal STR loci from Chinese Tujia ethnic group - Guo-lian Yuan; Chun-mei Shen; Hong-dan Wang; Wen-juan Liu; Guang Yang; Jiang-wei Yan; Hai-Xia Qin; Tong Xie; Hangyan Ran; Jie Yuan; Zuochun Liu; Bofeng Zhu (Molecular Biology Reports, 2012)

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Oxidative Damage of the Extracts of Condensate, Particulate and Semivolatile Organic Compounds from Gasoline Engine Exhausts on Testicles of Rats - Wangjun Che; Hong Qiu; Guiming Liu; Yun Ran; Hao Zhang; Li Zhang; Weihua Wen (Bulletin of Environmental Contamination and Toxicology, 2009)